Morphogenetic dispositions for variability in acute kidney injury after cardiac surgery: Pilot study - Karan, Radmila; Kovačević-Kostić, Natasa; Kirćanski, Bratislav; Čumić, Jelena; Terzić, Duško; Milićević, Vladimir; Velinović, Vojislav; Velinović, Miloš; Obrenović-Kirćanski, Biljana (Frontiers in Medicine, 2022)
Background: The aim of our study was to evaluate the degree of genetic homozygosity in cardiac surgical patients with postoperative acute kidney injury (AKI), compared to the subgroup without postoperative AKI, as well as to evaluate antropomorpho-genetic variability in cardiac surgical patients with regards to the presence and severity degree of AKI. Methods: The prospective cohort study included analysis of 138 eligible coronary artery disease (CAD) surgical patients that were screened consecutively. The tested group was divided into 3 subgroups according to RIFLE criteria: Subgroup NoAKI (N=91), Risk (N=31), and Injury (N=16). All individuals were evaluated for the presence of 19 observable recessive human traits (ORHT) as a marker of chromosomal homozygosity and variability. Results: Comparing subgroups NoAKI and Risk, 4 ORHTs were significantly more frequent in the Risk subgroup. Comparing subgroups NoAKI and Injury, 9 ORHTs were significantly more frequent in the Injury subgroup; while comparing Injury subgroup and Risk, 5 ORHTs were significantly more frequent in Injury than in Risk subgroup. Results also showed significant increase in the mean value of ORHTs for Injury subgroup compared to NoAKI subgroup (p=0.039). Variability decreased proportionally to the increase of the severity of AKI (VNoAKI=32.81%, VRisk=30.92%, VInjury=28.62%). Conclusions: Our findings pointed to the higher degree of recessive homozygosity and decreased variability in AKI patients versus NoAKI individuals, thus presumably facilitating development and severity degree expression of AKI in patients after cardiac surgery.